2018
DOI: 10.3390/cells7100163
|View full text |Cite
|
Sign up to set email alerts
|

AAA Proteases: Guardians of Mitochondrial Function and Homeostasis

Abstract: Mitochondria are dynamic, semi-autonomous organelles that execute numerous life-sustaining tasks in eukaryotic cells. Functioning of mitochondria depends on the adequate action of versatile proteinaceous machineries. Fine-tuning of mitochondrial activity in response to cellular needs involves continuous remodeling of organellar proteome. This process not only includes modulation of various biogenetic pathways, but also the removal of superfluous proteins by adenosine triphosphate (ATP)-driven proteolytic machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 127 publications
(236 reference statements)
1
25
0
Order By: Relevance
“…Mitochondrial AAA proteases couple energy derived from ATP hydrolysis to versatile functions. The article by Opalinska and Janska [8] reviews the literature of AAA proteases in yeast, plants and animals and highlights the numerous roles these proteases play.…”
Section: Mitochondrial Biologymentioning
confidence: 99%
“…Mitochondrial AAA proteases couple energy derived from ATP hydrolysis to versatile functions. The article by Opalinska and Janska [8] reviews the literature of AAA proteases in yeast, plants and animals and highlights the numerous roles these proteases play.…”
Section: Mitochondrial Biologymentioning
confidence: 99%
“…PHBs interact with OPA1 and m -AAA proteases in order to maintain an exact cristae morphology and regulate the mitochondrial protein expression levels. Mutations in the OPA1 gene cause neurodegeneration in autosomal dominant optic atrophy [97], while mutations in m -AAA protease subunits cause spinocerebellar ataxia, hereditary spastic paraplegia, and a spastic-ataxia neuropathy syndrome [98]. It goes without saying that PHB loss can be deleterious for neuron cells.…”
Section: Pathological Role Of Prohibitinsmentioning
confidence: 99%
“…Mitochondrial ATPases associated with diverse cellular activities (AAA) proteases located in the IM are crucial for mitochondrial homeostasis and are subdivided into intermembrane space AAA (i‐AAA) proteases and matrix AAA (m‐AAA) proteases depending on the location of their active sites. In humans, m‐AAA proteases are homo‐ or hetero‐oligomeric proteins composed of ATPase family gene 3‐like protein 2 (AFG3L2) and paraplegin (Spg7), whereas i‐AAA proteases consist of homo‐oligomeric Yme1L proteins . Together with AAAs, the ATP‐independent peptidase Oma1, also located in the IM, participates in mitochondrial dynamics through the processing of Opa1 …”
Section: Introductionmentioning
confidence: 99%
“…In humans, m-AAA proteases are homo-or hetero-oligomeric proteins composed of ATPase family gene 3-like protein 2 (AFG3L2) and paraplegin (Spg7), whereas i-AAA proteases consist of homo-oligomeric Yme1L proteins. 11 Together with AAAs, the ATP-independent peptidase Oma1, also located in the IM, participates in mitochondrial dynamics through the processing of Opa1. 12 In this study, we demonstrated that muscle atrophy was closely related to an imbalance in the mitochondrial quality control system.…”
mentioning
confidence: 99%